The Development of Health Technology Assessment in Taiwan: Perspectives and Analysis - Raoh-Fang Pwu; Yen-Shu Cheng; Wen-Wen Yang; Grace Hui-Min Wu (Taylor & Francis Group, 2023)
Efforts to advance health technology assessment (HTA) in Taiwan have aimed to optimize the allocation of National Health Insurance (NHI) resources. This study documents and analyzes the historical timeline of Taiwan's efforts in HTA, identifying areas to advance the HTA system, such as gaining broad stakeholder acceptance. We document ambitious plans to establish a larger, independent HTA center and how these plans did not materialize. The historical timeline also describes the primary focus of HTA shifting to serve the needs of decision-making authorities and committees. We argue that these changes resulted in growth of the HTA system, but also led to significant external criticism and potential compromise of its foundational principles. The inability to create a national HTA center can be attributed to several factors, including an immature ecosystem of HTA-Policy-Patient-Provider-Academic collaboration, a lack of a supportive culture, and challenging political and economic conditions. Nevertheless, if effectively managed, Taiwan's current HTA system could play a crucial role in rational decision-making, informed choices, and efficient NHI resource management. We argue that greater autonomy is crucial for enhancing financial sustainability and protecting against external influences to ensure objective and credible assessments. Additionally, we emphasize the importance of fostering a conducive learning environment to improve methodological expertise.